Dinamika Kehidupan Beragama Kaum Nahdiyin-Salafi di Pamekasan Madura - Hasan, Nor (Program Pascasarjana UIN Sunan Ampel Surabaya, 2013)
In principle, the Salafi-Islam attempts to call for genuine Islamic teaching as practiced during the period of the Prophet. Salafi-Islam came to Indonesia in the late nineteenth and early twentieth centuries, then spread to different places in the Archipelago. In Larangan, Pamekasan, the spread of Salafi-Islam is still in its nascent stage, from person-to-person, and appears as a small phenomenon in the midst of predominantly mainstream Islam. Salafi teachings spread through different forms of communication media (radios, televisions, magazines, and books) and religious practices of its Â proponents. The movement manifests itself in the pratices of rituals, not in politics. The implication of encounter between salafi-Islam and NU as the mainstream religious group in Pamekasan is as follows: (1) religous life in Pamekasan becomes more dynamic; (2) there emerges inward-looking attitude at their own religous practices as well as outward-looking attitude to the others. This phenomenon can be observed among more educated members of the society. Among the common people, however, there are two types of attitude: ignorance and negative reaction; and (3) an attempt to search for the common ground and dialogue among different religious communities is being conducted.